Notes on Onciderini (Coleoptera, Cerambycidae, Lamiinae): description of a new species of Lesbates Dillon & Dillon and new distribution records - Barros, Rafael C.; Julio, Carlos E. A.; Nearns, Eugenio H. (Zootaxa, 2019)
Lesbates chavesi sp. nov. is described and a key to species of the genus is presented. In addition, nine new records of Onciderini for the states of Rio de Janeiro and Paraná (Brazil) are provided.